Insolvency and bankruptcy: the theoretical aspect and emergence preconditions (Путеводитель предпринимателя)
Article is devoted to theoretical questions offorecasting of insolvency and bankruptcy of the companies. However the inaccuracy of interpretation of these concepts as uniform terminological design, in many respects explains and the developed stereotypes by definition of their economic essence.